(untitled) (Heritage, 2021)
This paper focuses on the research of the negated aorist tense in the novels written by the Serbian authors. Our goal was to prove if the negated aorist can show prospective with the given temporary reference. We established with the analysis of the example from the chosen corpus that there are essential terms for the negated predicate in the aorist to occur. Namely, it has to refer to non-appearance expected events that a narrator observes using senses. A narrator’s immediate cognition that things did not occur naturally is a mental event that has its own temporary reference. In fact, the scenes of the real events intertwine with the mental ones in narration, which are the reaction to the explicitly given event that does not take place, and that a narrator designates just because he/she expects it to happen. In that way, the immediate connection occurs between a narrator and a reader: lack of occurrence of the usual events indicates the plot and the turn of the events and creates tension, suspense, and astonishment in a reader.